The Style of the 1890s: Art Nouveau design in New Zealand Architecture - Lochhead, Ian (Architectural History Aotearoa, 2007)
The influence of Art Nouveau on New Zealand architecture has generally been considered to be negligible but its impact was nevertheless significant during the period from 1890 to the outbreak of the First World War. Across a wide range of building types, from large scale public buildings to modest houses, Art Nouveau-inspired door pulls, dados, embossed ceilings, leaded glass and tiles abound. This paper explores the largely hidden presence of Art Nouveau in New Zealand architecture of this period and considers the reasons why buildings that otherwise have little connection with the style incorporate features that are often strikingly disparate in aesthetic terms. Is this because New Zealand architects and builders simply did not understand the aesthetic implications of their actions? Was it a consequence of remoteness from centres of architectural innovation or the result of purchasing items, magpie-like, from architectural catalogues? Or was it, indeed, the result of a desire to achieve an aura of "instant sophistication"?